Effect size test of 7e learning cycle model: conceptual understanding and science process skills on senior high school students. (June 2020) - Komikesari, H; Anggraini, W; Asiah, N; Dewi, P S; Diani, R; Yulianto, M N
Abstract: This study aims to determine the effectiveness of the 7E Learning Cycle Model of conceptual understanding and science process skills students. The research method used a quasi-experiment with a non-equivalent control group design. The population in this study were students of class XI IPA Senior High School 9 Bandar Lampung. From the analysis of the hypothesis test showed that t-count obtained a result of 4.838 while t-table of 2.002 according to the provisions if the value of t-count> t-table then H0 was rejected and H1 was accepted. Based on these provisions, it means that there is an effect of the use of the Learning Cycle Type 7E model on the ability of students to understand the concepts. Analysis of science process skills shows that t-count is 2.074 while t-table is 2.002 and according to existing criteria, if the value of t-count>t-table then H0 is rejected and H1 is accepted, and its effectiveness is known by the effect test of the size which is getting a d value of 1.53 with a high category. The conclusion is the application of the 7E Learning Cycle Model is effective in improving conceptual understanding and science process skills.